Analizar la demanda eléctrica por la incorporación de las cocinas de inducción y el calentador eléctrico de agua, del alimentador Píllaro centro de la Empresa Eléctrica Ambato S.A en el año 2015 - Chizaguano Tituaña, Jorge Alfredo (2015)
In Ecuador, the main source of energy for cooking food and heating water in homes is Liquefied Petroleum Gas (LPG) which is a fundamental and necessary for each tool citizens through the development of projects hydropower, the country has the ability to change the conventional kitchens for induction cookers, for that reason the study of the implementation of induction cookers and electric water heaters in the feeder Píllaro Center Tungurahua province was conducted. El Alimentador Píllaro Center has about 4159 residential users was applied in order to regard the change of gas stoves for the gas subsidy, this survey detailed that 43% of respondents agree to make this change, additional replacement of water heaters are looking for efficient electric water heating systems to replace partially or completely the use of Liquefied Petroleum Gas subsidized. Through this study, the increased demand for future years was projected from the present to 2020 year....